2017
DOI: 10.2298/psi161203008o
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the physical education attitude scale for adolescents

Abstract: The goal of this research was to develop and validate a physical education (PE) attitude scale (PEAS) for students in early and middle adolescence, based on the contemporary theories of attitudes as a summary evaluation of different information related to the attitude object. In the first study, preliminary version of the scale was administrated on the sample of 547 students. Principal component analysis (PCA) revealed 4 factors, named Satisfaction, Comfort, Activity and Teacher. Second order PCA showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
1
9
3
Order By: Relevance
“…The findings confirm some in previous studies (Subramaniam and Silverman, 2007;Scrabis-Fletcher et al, 2016;Marttinen et al, 2018), which found no sex differences in PE attitudes. However, the current results also contradict other studies, which revealed that female students (Zeng et al, 2011;Pereira et al, 2020) or male students (Koca and Demirhan, 2004;Koca et al, 2005;Mercier et al, 2017;Orlić et al, 2017) had more positive attitudes toward PE compared with their counterparts. Furthermore, our findings did not support the findings of studies that reported that students with PA outside school had more positive attitudes toward PE than those who did not (Orlić et al, 2017(Orlić et al, , 2018Pereira et al, 2020).…”
Section: Influence Of Student and Teacher Sex Grade Level And Pa Oucontrasting
confidence: 99%
See 4 more Smart Citations
“…The findings confirm some in previous studies (Subramaniam and Silverman, 2007;Scrabis-Fletcher et al, 2016;Marttinen et al, 2018), which found no sex differences in PE attitudes. However, the current results also contradict other studies, which revealed that female students (Zeng et al, 2011;Pereira et al, 2020) or male students (Koca and Demirhan, 2004;Koca et al, 2005;Mercier et al, 2017;Orlić et al, 2017) had more positive attitudes toward PE compared with their counterparts. Furthermore, our findings did not support the findings of studies that reported that students with PA outside school had more positive attitudes toward PE than those who did not (Orlić et al, 2017(Orlić et al, , 2018Pereira et al, 2020).…”
Section: Influence Of Student and Teacher Sex Grade Level And Pa Oucontrasting
confidence: 99%
“…This result confirms our hypothesis 1, suggesting that Filipino students generally have pleasant experiences and feelings toward PE and perceive the subject as valuable. These findings corroborate Orlić et al (2017)'s research, who examined PE attitude of Serbian students using PEAS; they found that the mean scores for PE attitude (3.81) and the dimensions of satisfaction (3.82), activity (3.64), and teacher (3.55) were moderately positively high. Nonetheless, in their study, the comfort dimension showed a higher score (mean score of 4.14).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations